Sustainable Optimization of Mold Heating: A Dual Approach with SWARA and MARCOS Methods - Peker, Rahim Can; Karakurt, Asim Sinan (GAZI UNIV, 2024)
There are many methods and raw materials used in the manufacture of Fiber Reinforced Plastics (FRP) by hot molding, such as Sheet Molding Compound (SMC), Bulk Molding Compound (BMC), and Prepreg fabrics. In most applications, it is common practice to insert the new dough into the mold without cooling it, then re-press and cure. Placing the mold in the dough without cooling causes the surface of the molded product to cure faster than the inner region, resulting in a structurally discontinuous structure in the product. Therefore, in more professional production, the mold is lowered to around 120 oC and the dough is poured into the mold at this stage. However, this increases energy consumption and carbon emissions for the heating and cooling phases. This study investigated the energy efficiency of the production of FRP using the hot-pressing process. At the end of this study, by using alternative energy methods in the manufacturing processes, results such as investment costs, depreciation costs, reductions in bills, and carbon emissions were achieved. To find the best alternative from these results, the criteria weights were determined using SWARA, and the alternatives identified were ranked using the MARCOS method. As a result of this ranking, the best alternative was determined to be a 40 kWh battery and a 25 kW solar panel option among the solar panel power and battery capacity alternatives.
Keywords: Energy efficiency; Hot press manufacturing; Multi-Criteria Decision Making; Optimization; HEATING/COOLING CHANNELS; COOLING SYSTEM; OPTIMAL-DESIGN; SELECTION; Science & Technology - Other Topics